Study Program Selection Modeling With Simple Additive Weight (SAW) Method - Agung Setiawan; Detri Amelia Chandra (YCMM, 2022)
The suitability of choosing study programs in higher education will have an impact on the quality of graduates who have competence. This study aims to analyze and design a decision support system that can be used as a reference in choosing a study program that suits students' abilities. Data was collected through the observation method, then the multi Attribute Decision Making (MADM) method was used to process several criteria, namely academic scores, ability test scores and language tests for several students who were going to continue their studies to college. The system is designed using the Simple Additive Weight (SAW) method. While the data processed is academic scores in the form of student report cards, MIPA ability tests (Mathematics, Physics, Chemistry and biology) and language tests (Indonesian and English). The results of the study indicate that the designed decision support system can produce information on the priority of study programs in accordance with students' abilities, so that it can be used as a basis for decision making in the selection of study programs.